The Relationship Between Emotional Intelligence and Verbal Aggressive Behavior of Junior High School Students - Nissa, Siti Nurun; Isfahani, Rizki (Jurnal Pendidikan Indonesia Gemilang, 2024)
Verbal aggression is a form of communication that damages the self-concept of others, frustration, embarrassment, anxiety, and anger, and can also damage relationships so that it can cause physical aggression. This study aimed to determine the relationship between emotional intelligence and verbal aggressive behavior of junior high school students. The research design in this study is quantitative research with observational analysis, a study of the Cross-sectional approach. The sampling technique used a proportionate stratified random sampling of 164 respondents of junior high school students at an Islamic junior high school in Tangerang District, Indonesia. Data analysis using the Spearman Correlation Test. Based on the study's results, most respondents with high emotional intelligence amounted to 83 respondents (50.6%), and the results of low verbal aggressive behavior amounted to 96 (58.5%). The results of the Spearman rho test obtained a significance value of 0.0000.05, so it can be said that H0 is rejected, it can be said that there is a relationship between emotional intelligence and verbally aggressive behavior with a correlation of -0.674 coefficient, it is said to be a strong correlation with the direction of negative correlation.